WAYS TO REDUCE THE ACCOUNTING COSTS OF AGROCLUSTER IN THE CONDITIONS OF GLOBAL CLIMATE CHANGE - Khaydarova Shoira Nishanbayevna (Journal of Artificial Intelligence and Digital Economy, 2024)
Objective: This study explores the agrocluster system in Uzbekistan, emphasizing its role in enhancing agricultural productivity, economic resilience, and export potential. By integrating production, processing, and distribution, agroclusters aim to modernize agriculture, addressing regional and global challenges. Methods: A mixed-method approach was employed, combining qualitative and quantitative analyses. Key strategies included examining international agrocluster practices, assessing regional limitations such as infrastructure and land productivity, and analyzing cost structures to develop cost-minimization strategies. Results: Findings highlight the socio-economic significance of agroclusters, showcasing their ability to reduce operational inefficiencies, foster innovation, and streamline collaboration among stakeholders. Challenges like climate change and infrastructure constraints were identified, necessitating robust strategies for sustainable development. Novelty: This research emphasizes the compact integration of agrocluster participants and introduces cost-efficient measures through digital transformation, fixed-variable cost analysis, and innovative farming technologies, offering actionable insights to enhance Uzbekistan’s agrocluster efficiency.